PERANCANGAN SENTRA KACANG KEDELAI, PABRIK TAHU MODERN BERGAYA ARSITEKTUR INDUSTRIAL - Cheris, Rika; Basyir, Abdul; Rizal, Yose (INSIDE : Jurnal Desain Interior, 2025)
Traditional tofu factories in Indonesia still rely on conventional processing methods, which often affect product quality and contribute to environmental pollution. This study proposes the integration of a Soybean Center, tofu factory, restaurant, and retail kiosk within a single complex using the principles of Industrial Architecture. This approach emphasizes functional workspace efficiency, optimal material utilization, and introduces soybean education for visitors. The research adopts a qualitative method with a descriptive approach, involving direct observations of traditional tofu factories to understand production, operational, and environmental requirements. The objective is to develop a multifunctional building design that balances functional, aesthetic, economic, production, and environmentally friendly aspects. The design outcome is expected to create a modern tofu factory that enhances product quality, reduces environmental impact, and supports local food education, while simultaneously opening economic opportunities through an integrated restaurant and retail kiosk within a cohesive industrial architectural concept.